Correlation Between Children’s Temperament and Risk Factor of Attention Deficit/Hyperactivity Disodrer in Elementary School - Cheifia Krissanti Sasono; Yunias Setiawati; Irwanto Irwanto (Biomolecular and Health Science Journal, 2019)
Introduction: The main symptoms of Attention-Deficit/Hyperactivity Disorder (ADHD) are hyperactivity, impulsivity, and inattention. While temperament in children with ADHD is described as high in negative reactivity, low task persistence, high activity, low attentional focusing, high impulsivity and low inhibitory control. This study aims to analyze the correlation between children’s temperament and risk factor of ADHD.Methods: This study used cross-sectional design with Abbreviated Conners’ Rating Scale and Temperament in Middle Childhood questionnaire for instrument. All data are analyzed using Pearson correlation.Results: Prevalence of children with risks of ADHD from total subject was 21/114 students (18,4%, consisted of 18 males (81%) and 3 females (19%) with average age was 10 years old. The majority of participants were in the sixth grade (28.6%). There was a positive and weak correlation between surgency and ADHD symptoms (3,05 ± 0,75, p=0,045; r=0,44).Conclusion: There was no significant correlation between the negative affect and effortful control dimensions of temperament with severity of ADHD, however this study found a positive and weak correlation between surgency and risk factor of ADHD.